The reliability of thromboelastography in a simulated rotary wing environment. Issue 12 (29th August 2018) - Scott, Robert; Burns, Brian; Ware, Sandra; Oud, Floris; Miller, Matthew
Abstract : Background: With the increasing role of point-of-care coagulation testing in trauma, we sought to test the reliability of the thromboelastography (TEG)6s machine in a simulated rotary wing environment. Method: A two-arm study was conducted, running TEG6s quality control cartridges in a helicopter flight simulator with realistic vibration and in stable ground conditions. The flight conditions during testing included take-offs, landings and inflight emergencies such as engine failures. TEG values for R time, K time, α-angle and maximum amplitude (MA) were collected and compared with manufacturers' normal ranges. Results: 148 TEG samples were included for analysis (72 simulator arm, 76 ground arm). In the simulator arm, four of our K time values fell below the normal range and four MA values were above the normal range. All other values in both simulator and ground arms were in the normal range. Conclusion: The TEG6s is a viable technology in the simulated rotary wing environment, and it is feasible to conduct further studies using human blood in live rotary wing conditions. Extreme flight conditions should be avoided during further testing.